Time and commitment: the grammaticalization of uúch in Lakandon Maya - Henrik Bergqvist (Journal de la Société des Américanistes)
The paper accounts for the grammaticalization of uúch, (‘previously’, ‘long ago’) from a one-place predicate in Yukatek Maya meaning ‘to happen’, to a cognate adverbial in Lakandon Maya denoting ‘knowledge asymmetry’; a change from subjective ‘time’ to intersubjective ‘knowledge’. The paper proposes an analysis of uúch and the contrasting kuúch/ka’ch as operators of second-order stance, using a Jakobsonian model for analyzing verbal categories forwarded by Paul Kockelman (2004) to operationalize the notion of stance, as visible in Q’eqchi’ modals. Intersubjectification as a process of language change aligns with Kockelman’s original suggestion that first-order stances may be embedded to produce second-order stances, i.e. “stance about stance”.